Educational Game-Based Learning Media to Grow Learning Motivation in Computer and Basic Network Subjects in Vocational High Schools - Faiz, Yoga Hanif; Kurniawan, Wendy Cahya (Universitas Negeri Malang, 2023)
The use of technology in the learning process requires educators to be able to adapt to technology in the learning process. Based on the observations that have been made, in the Subject of Computers and the basic network of computer assembly shows that students are less motivated. To foster motivation to study computer assembly material, media was developed to discuss basic competencies regarding computer assembly tools. Researchers make Educational Game-Based Learning Media as Learning Media that adapts to digital technology. This media has many advantages, including being easy to operate, not limited by distance and space, not boring, and easy to understand. The purpose of this development research is to develop and determine the feasibility of Educational Game-based learning media to foster motivation to learn basic subjects of Computers and Networks in TKJ. The research and development method used is Design Thinking with the following stages: 1) Empathize; 2) Define; 3) idea; 4) Prototype; 5) Test. The types of instruments used are game test questionnaires and student learning motivation tests. The type of data in this study is quantitative and quantitative with data collection methods using questionnaires. The results of the research and development carried out produced educational game learning media for computer subjects and basic network computer assembly materials. Feasibility analysis on material validation 96.45 percent, media expert validation 96.46 percent, product trial 84.23 percent, and learning motivation test 84.38 percent. Based on the results of the feasibility analysis of Educational Game learning media it is said to be